Extra pulmonary tuberculosis manifestation in head and neck and its diagnosis with recent tools like cartridge based nucleic acid amplification test - Vatsyayan, Richa; Sachdeva, Kavita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The study aimed to assess the clinical manifestations of extra-pulmonary tuberculosis (head and neck) in diagnosed pulmonary tuberculosis (TB) patients and without pulmonary TB and to determine the sensitivity and specificity of cartridge based nucleic acid amplification test (CBNAAT) in the diagnosis of extra-pulmonary TB. Methods: The study was conducted as an observational study at the Department of Otorhinolaryngology, tertiary care center, Jabalpur (Madhya Pradesh) for a period of 18 months i.e. from 01 March 2019 to 31 August 2020 on 30 patients presenting with lesions in ear, nose and throat (ENT), head and neck region. All necessary investigations with TB workup were done. Sputum samples were analyzed by CBNAAT on Xpert- Mycobacterium tuberculosis complex/resistance to rifampin (MTB/RIF). Patients were treated accordingly. Appropriate surgical intervention was done in necessary cases. Using statistical analysis, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy was calculated for CBNAAT. Results: Neck swelling and ear discharge were the most common features observed in 66.7% of cases. In cases with pulmonary TB, systemic features were the most predominant features whereas in cases with extra-pulmonary TB, local features were predominant. Sensitivity, specificity, PPV and NPV of CBNAAT were documented to be 85%, 50%, 89.5% and 40% respectively. Conclusions: TB of the head and neck are commonly encountered in clinical practice. The patients usually present with variable clinical manifestations depending upon the site of involvement. The middle ear is the most common site affected by head and neck tuberculosis. CBNAAT is a sensitive tool for the diagnosis of extra-pulmonary TB with and without associated pulmonary TB.